Product of Roots of Sums of Products of Differences

Algebra Level 3

What is the product of all roots to the equation

( x 1 ) ( x 2 ) ( x 3 ) + ( x 2 ) ( x 3 ) ( x 4 ) + ( x 3 ) ( x 4 ) ( x 5 ) + ( x 4 ) ( x 5 ) ( x 6 ) + ( x 5 ) ( x 6 ) ( x 7 ) + ( x 6 ) ( x 7 ) ( x 8 ) = 0 ? \begin{aligned} & (x-1)(x-2)(x-3) + (x-2)(x-3)(x-4) \\ + & (x-3)(x-4)(x-5) + (x-4)(x-5)(x-6) \\ + & (x-5)(x-6)(x-7) + (x-6)(x-7)(x-8) =0 ? \end{aligned}

Details and assumptions

Clarification: Make sure you scroll to the right (if need be) to see the full equation. This problem ends with a "?".


The answer is 126.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

10 solutions

Ahmad Widardi
May 20, 2014

This equation will be formed in a x 3 + b x 2 + c x + d = 0 ax^3+bx^2+cx+d=0 . This equation has 3 roots let's say p , q , r p,q,r .

Using Vieta theorem we will get p + q + r = b / a , p q + q r + p r = c / a , p q r = d / a p+q+r = -b/a, pq+qr+pr = c/a, pqr = -d/a . We are just asked to find the value of p q r pqr , so need to determine d d and a a . Because d d is a constant so we'll get d d equals to ( 1 ) ( 2 ) ( 3 ) + ( 2 ) ( 3 ) ( 4 ) + ( 3 ) ( 4 ) ( 5 ) + ( 4 ) ( 5 ) ( 6 ) + ( 5 ) ( 6 ) ( 7 ) + ( 6 ) ( 7 ) ( 8 ) = 756 (-1)(-2)(-3) + (-2)(-3)(-4) + (-3)(-4)(-5) + (-4)(-5)(-6) + (-5)(-6)(-7) + (-6)(-7)(-8) = -756 . Because a a is the coefficient of x 3 x^3 so we'll get a a equals to 1 + 1 + 1 + 1 + 1 + 1 = 6 1+1+1+1+1+1 = 6 . So we get p q r = d / a = ( 756 ) / 6 = 126 pqr = -d/a = -(-756)/6 = 126 . So the product of all roots to the equation is 126.

The quick way to determine the constant of a polynomial is to evaluate at 0. There is no need to expand the entire polynomial out.

Calvin Lin Staff - 7 years ago
Shreyam Natani
May 20, 2014

(x-a)(x-b)(x-c) = x³ – (a+b+c)x² + (ab+bc+ca)x – abc

We can express all the six polynomials in this manner and add them up to get:

6x³ - i = 1 6 \displaystyle \sum_{i=1}^6 ( a i + b i + c i a_i + b_i + c_i )x² + i = 1 6 \displaystyle \sum_{i=1}^6 ( a i . b i + b i . c i + c i . a i a_i.b_i + b_i.c_i + c_i.a_i )x - i = 1 6 \displaystyle \sum_{i=1}^6 ( a i . b i . c i a_i . b_i . c_i ) = 0

Now we know that the product of the roots of an cubic polynomial ax³ + bx² + cx + d = 0 can be given as d a \frac {-d}{a}

Using this knowledge we can see that the product of the roots of the above polynomial can be expressed as ( i = 1 6 ) ( ( a i . b i . c i ) 6 \frac {(\displaystyle \sum_{i=1}^6)((a_i.b_i.c_i)}{6} .

Here by calculation we get i = 1 6 \displaystyle \sum_{i=1}^6 ( a i . b i . c i a_i.b_i.c_i ) as 756 .

Hence the product of the roots is 126

Lê Minh Thắng
May 20, 2014

The equation can be rewritten in the form: 3 ( 2 x 9 ) ( x 2 9 x + 28 ) = 0 3(2x-9)(x^2-9x+28)=0 which has one real root x = 9 2 x=\frac{9}{2} . The other 2 roots of the equation x 2 9 x + 28 = 0 x^2-9x+28=0 have the product equal to 28 (by Viete). So the product of all roots is 126.

Duc Minh Phan
May 20, 2014

Suppose that the L.H.S. of the given equation can be expand as a 3 x 3 + a 2 x 2 + a 1 x + a 0 a_3x^3+a_2x^2+a_1x+a_0 . By using Vieta's formulas, we obtain that the product P P of all roots to the given equation is equal to a 0 a 3 -\frac{a_0}{a_3} . It is easy to see that a 3 = 6 a_3 = 6 and a 0 = i = 1 6 i ( i + 1 ) ( i + 2 ) = 756 a_0 = \sum_{i=1}^6 i(i+1)(i+2) = -756 . Therefore P = 756 6 = 126 P = \frac{756}{6}=126 .

Sudipta Patowary
May 20, 2014

each term is a cubic expression of the form (x-a)(x-b)(x-c). The roots of each expression are a,b and c. For example the first term is (x-1)(x-2)(x-3), so its roots are 1,2 and 3. The product of roots of a cubic equation is given by -(coefficient of x^0)/(coefficient of x^3). Here, coefficient of x^3 is 1. And product of roots is 1 2 3=6. So the cubic expression of which these are roots is given by x^3+.........-6. Similarly the constants of the other five cubic expressions can be found in a similar way. They are -24,-60,-120,-210 and -336, respectively. So the combined constant of the given equation is the sum of all these constants i.e. -6+-24+-60+-120+-210+-336=-756. So the resulting cubic expression has a constant term of -756. However, the coefficient of x^3 in this case is 6, as the equation is composed of six cubic expressions. So, product of roots=-(-756)/6=126.

Raghunathan N.
May 20, 2014

Expand the given expression completely to get a cubic equation :

2x^3 - 27x^2 + 137x - 252 = 0.

In this case we get the product of all three roots as

-constant term / (coefficient of x^3). That gives 252 / 2 = 126.

King Singh
May 20, 2014

In the given question, we will observe that on opening all the brackets the given expression will take the form - ax^3 + bx^2 + cx^1 + d = 0

For such cubic expressions :- Product of the roots is given by -d/a

So to find the given result we will just have to get the ( )x^3 and the constant term

By simple observation we will get the result as

6x^3 + ( unwanted term )x^2 + ( unwanted term )x^1 + ( constant - d)

constant term is -{ 1 2 3 + 2 3 4 + 3 4 5 + 4 5 6 + 5 6 7 + 6 7 8 } constant term = d= -756

So product of roots is -(-756)/6 = 756/6 = 126

Tunk-Fey Ariawan
Jan 25, 2014

The equation in the question above can be written as 6 x 3 81 x 2 + 411 x 756 = 0 3 ( 2 x 9 ) ( x 2 9 x + 28 ) = 0 ( 2 x 9 ) ( x 2 9 x + 28 ) = 0 \begin{aligned} 6x^3-81x^2+411x-756 &=0 \\ 3(2x-9)(x^2-9x+28) &=0 \\ (2x-9)(x^2-9x+28) &=0 \end{aligned} Then we have 2 x 9 = 0 x 1 = 9 2 \begin{aligned} 2x-9 &=0\\ x_1 &= \frac{9}{2} \end{aligned} and x 2 9 x + 28 = 0 x 2 9 x = 28 ( x 9 2 ) 2 81 4 = 28 ( x 9 2 ) 2 = 28 + 81 4 x 9 2 = 31 4 x 9 2 = ± 1 2 i 31 x = 1 2 ( 9 ± i 31 ) x 2 = 1 2 ( 9 + i 31 ) ; x 3 = 1 2 ( 9 i 31 ) \begin{aligned} x^2-9x+28 &=0 \\ x^2-9x &=-28\\ \left(x-\frac{9}{2}\right)^2 -\frac{81}{4}&=-28\\ \left(x-\frac{9}{2}\right)^2 &=-28+\frac{81}{4}\\ x-\frac{9}{2} &= \sqrt{-\frac{31}{4}}\\ x-\frac{9}{2} &= \pm \frac{1}{2}i \sqrt{31}\\ x &= \frac{1}{2} (9 \pm i \sqrt{31})\\ x_2 &= \frac{1}{2} (9 + i \sqrt{31}) \text{ ; } x_3 = \frac{1}{2} (9 - i \sqrt{31}) \end{aligned} Finally, x 1 x 2 x 3 = 9 2 1 2 ( 9 + i 31 ) 1 2 ( 9 i 31 ) = 9 8 ( 9 2 ( i 31 ) 2 ) = 9 8 ( 81 + 31 ) = 126 \begin{aligned} x_1 \cdot x_2 \cdot x_3 &= \frac{9}{2} \cdot \frac{1}{2} (9 + i \sqrt{31}) \cdot \frac{1}{2} (9 - i \sqrt{31})\\ &= \frac{9}{8}(9^2 - (i \sqrt{31})^2)\\ &= \frac{9}{8}(81 + 31)\\ &= \boxed{126} \end{aligned}

# Q . E . D . # \text{\# }\mathbb{Q}.\mathbb{E}.\mathbb{D}.\text{\#}

You might want to check out this article on Vieta's Formulas . What these do is allow you to find the product of the roots of a polynomial without actually finding the roots. Notice that your cubic can be written as c ( x r 1 ) ( x r 2 ) ( x r 3 ) c(x-r_1)(x-r_2)(x-r_3) where r 1 , r 2 , r 3 r_1,r_2,r_3 are your roots and c c is a constant. Expanding this out we find that the constant term is c r 1 r 2 r 3 -cr_1r_2r_3 . Take a look at the cubic you found in this problem. We know that c = 6 c = 6 since it is the leading coefficient, and we know 6 r 1 r 2 r 3 = 726 -6r_1r_2r_3 = -726 or r 1 r 2 r 3 = 126 r_1r_2r_3 = 126 . Notice we've found the product of the roots without tedious factoring and use of the quadratic formula.

Logan Dymond - 7 years, 4 months ago

If p ( x ) = a x 3 + b x 2 + c x + d p(x) = ax^3 + bx^2 + cx + d , then the product of the roots is d / a -d/a .

To find d d we may evaluate p ( 0 ) = ( 1 2 3 ) + ( 2 3 4 ) + + ( 6 7 8 ) = 3 ! ( ( 3 3 ) + ( 4 3 ) + ( 5 3 ) + + ( 8 3 ) ) = 3 ! ( ( 9 4 ) ) = 756 p(0) = (-1\cdot-2\cdot-3 )+(-2\cdot-3\cdot-4)+\cdots+(-6\cdot-7\cdot-8) = -3!(\binom3 3 +\binom 4 3 +\binom 5 3+\cdots+\binom 8 3) = -3!(\binom9 4) = -756 .

To find a a we may consider p ( 1 x ) p(\dfrac1 x) : ( 1 x 1 ) ( 1 x 2 ) ( 1 x 3 ) + + ( 1 x 6 ) ( 1 x 7 ) ( 1 x 8 ) = ( 1 x ) ( 1 2 x ) ( 1 3 x ) + + ( 1 6 x ) ( 1 7 x ) ( 1.8 x ) (\dfrac1 x -1)(\dfrac1 x -2)(\dfrac1 x -3) +\cdots+(\dfrac1 x -6)(\dfrac1 x - 7)(\dfrac1 x -8) = (1-x)(1-2x)(1-3x)+\cdots+(1-6x)(1-7x)(1.8x) . Evaluating in 0 0 gives us a = 6 a=6 . Hence the product is ( 756 ) / ( 6 ) = 126 -(-756)/(6)=126 .

Aman Jaiswal
Feb 4, 2014

After expanding i got : 6x^3-81x^2+421=756 and we know that product of roots is constant term divided by coefficient of term with highest power i.e 756/6=126

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...